Crosstalk between liver macrophages and gut microbiota: An important component of inflammation-associated liver diseases - Zhou, Ziyuan; Pan, Xiaxia; Li, Lanjuan (Frontiers in Cell and Developmental Biology, 2022)
Hepatic macrophages have been recognized as primary sensors and responders in liver inflammation. By processing host or exogenous biochemical signals, including microbial components and metabolites, through the gut-liver axis, hepatic macrophages can both trigger or regulate inflammatory responses. Crosstalk between hepatic macrophages and gut microbiota is an important component of liver inflammation and related liver diseases, such as acute liver injury (ALI), alcoholic liver disease (ALD), and nonalcoholic fatty liver disease (NAFLD). This review summarizes recent advances in knowledge related to the crosstalk between hepatic macrophages and gut microbiota, including the therapeutic potential of targeting hepatic macrophages as a component of gut microecology in inflammation-associated liver diseases.